Privacy Concerns, Content Information and its impact on the Adoption and Use of Fintech in Indonesia: The Mediating Role of Functional Values - Sinulingga, Nora Anisa Br (Universitas Bangka Belitung, 2025)
The aim of this study was to analyse privacy concern and content information on adoption and use Fintech among Generation Z and Y in Indonesia through functional value as mediation. This research uses a quantitative approach conducted by distributing questionnaires via google forms. The population of this study were all e-wallet users in generations Z and Y who were in Indonesia and the selection of respondent samples using the probability sampling methods, namely proportional random sampling, totals of 420 respondents. Data analysis methods and hypothesis testing used descriptive statistical analysis and inferential statistical analysis, namely Structural Equation Model (SEM) with Structural Partial Least Square (SEM-PLS) analysis method. The results of this study discover that privacy concern has a positive but insignificant effect on adoption and use FinTech. Content information, functional value reliability and customer interaction have a positive and significant influence. This research model can serve as a reference for researchers related to service dominant logic and the adoption and use of FinTech.